Readings in cultural diversity and criminal justice - Ross, Lee E. (Anthology series for teaching, 2020)
"Readings in Cultural Diversity and Criminal Justice presents students with a collection of scholarly, interdisciplinary articles and invites them to critically examine the importance of cultural diversity within the criminal justice system. The book is divided into five parts. Part I consists of introductory articles that discuss colorism, the origins of racism, and how the media perpetuates racial stereotypes. In Part II, students read articles devoted to theory that advance their understanding of the intersections of diversity, racism, and crime. Part III focuses on the areas of policing, prosecution, and punishment. Part IV includes readings that address issues of cultural diversity within corrections and correctional settings. The articles in the final part speak to school discipline rates in the U.S., the dynamics of racial anxiety and the advantages enjoyed by most whites, and the avoidance of integration across the political spectrum. Throughout, post-reading questions encourage reflection, discussion, and further exploration of the material. Readings in Cultural Diversity and Criminal Justice is an ideal supplementary text for courses in criminology, criminal justice, and related disciplines." -- Publisher's website